328. The Basedow's disease radiometabolic therapy: The uptake volume estimation. (December 2018) - Ostinelli, A.; Duchini, M.; Cacciatori, M.; Frigerio, G.; Frigerio, M.; Gelosa, S.; Vassena, A.; Corso, A.; Martinelli, I.; Posterli, R.
Abstract : Purpose: The ASST Lariana has adopted a personalized approach to treat Basedow's hyperthyroidism, based on mathematical models describing the radioiodine uptake and the hypercaptant mass evaluation. Functional parameters are derived from the thyroid uptake of a trace activity. The target volume is generally estimated by a 99m Tc-pertechnetate planar scintigraphy. The aim of this study was to investigate the contribution of SPECT/CT images, both by the analysis of the processed thyroid images with a home-made software and by a inter-operator comparison. Methods: SPECT/CT images of 46 patients with Basedow's disease were acquired by injecting 185 MBq of 99m Tc-pertechnetate. SPECT images were reconstructed using both Filtered Back Projection (FBP) and Ordered Subsets Expectation Maximization (OSEM) algorithms and varying the reconstruction parameters in order to find the optimized combination. Volumes were estimated by a in-house Matlab implementation of the Recovering Iterative Thresholding Method (see Fig.). Moreover, to assess the CT contribution, three nuclear physicians calculated the target volume of 20 patients, approximating the volume with a rotational ellipsoid. The statistical analysis was performed by IBM-SPSS Statistics 20 software (Kolmogorov–Smirnov test, T-test and ANOVA for paired data and interclass correlation coefficient (ICC)). Results: For the OSEM 3D algorithm a range of parameters was found within which volume estimation showed no statistically significant differences (3–6 subset range requires >12 iterations, subset >6 requires >4 iterations). For SPECT images only, the volumes Interclass Correlation Coefficient (ICC) was 0.43, while for SPECT/CT was 0.54, evidencing an increasing correlation degree. Conclusions: Firstly, this study identified the optimal reconstruction parameter range. Secondly, it demonstrated that SPECT/CT images allowed to integrate functional and morphological information, enhancing both the functional mass localization and the corrections for scattering and attenuation. Moreover, SPECT/CT images improved the nuclear physician ability in the functional volume estimation, increasing the inter-operator correlation.